PENAMBAHAN BEBERAPA JENIS GULA DAPAT MENINGKATKAN KUALITAS SPERMATOZOA BEKU ASAL EPIDIDIMIS TERNAK DOMBA (Addition of Various Sugars in Improving Quality of Frozen Thawed Epididymal Spermatozoa of Ram) - Herdis, Herdis; Darmawan, I Wayan Angga; Rizal, Muhammad (Universitas Syiah Kuala, 2016)
ABSTRACT The purpose of this research was to examine the effect of various sugars addition in Tris extender on quality of frozen thawed epididymal spermatozoa of ram. Collected spermatozoa was divided into five tubes and centrifuged at 3,000 rpm for 30 minutes. Supernatants were removed and pellets were diluted with Tris extender (control), Tris extender + 0.4% dextrose (dextrose), Tris extender + 0.4% maltose (maltose), Tris extender + 0.4% lactose (lactose), and Tris extender + 0.4% sucrose (sucrose), respectively. There were no significantly difference among treatment on mean percentages of motile (MS), live (LS) and intact plasma membrane (IPM) after equilibration. Mean percentages of post-thawed MS, LS, and IPM for dextrose (43.0, 53.8, and 53.4%), maltose (44.0, 54.8, and 52.8%), lactose (44.0, 52.8, and 52.8%), and sucrose (44.0, 55.0, and 53.4%) were significantly (P0.05) higher than control (37.0, 44.0, and 40.8%). In conclusion, addition of 0.4% dextrose or 0.4% maltose or 0.4% lactose or 0.4% sucrose in Tris extender increased quality of frozen thawed cauda epididymal spermatozoa of ram.